APLASTIC ANEMIA ET CAUSA OF SUSPECT VIRAL HEPATITIS INFECTION: A CASE REPORT - Lismana, I Wayan Wawan (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Aplastic anemia is anemia that occurs because of a failure of hematopoiesis is relatively rare but can be life threatening. The cause of aplastic anemia itself is still largely unknown or idiopathic. Minority of cases mainly due to a virus infection, one of which is viral hepatitis has long been known to cause symptoms of aplastic anemia. This report discusses the suspected aplastic anemia caused by hepatitis virus infection. Course of the disease or the prognosis of aplastic anemia varies, but a poor prognosis may occur if not handled with good treatment
Keywords: aplastic anemia, hepatitis virus infection